Unlocking the link between company attributes and sustainability accounting in shanghai: firm traits driving corporate transparency and stakeholder responsiveness - Wang, Litao (Frontiers in Environmental Science, 2023)
Sustainability accounting is crucial for corporate transparency and responsibility, but its relationship with firm characteristics in Shanghai, China’s financial center, remains poorly understood. This study uses a descriptive-analytical methodology to examine the impact of firm size, industry type, and profitability on sustainability accounting practices. A systematic literature review and meta-analysis of 43 studies provide insights into the extent and drivers of sustainability reporting. The findings reveal a positive association between firm size (r = 0.389) and profitability (r = 0.327) with sustainability reporting. Larger, more profitable firms, including state-owned enterprises, exhibit extensive sustainability accounting practices. However, the effect of industry type is inconclusive (r = 0.061), indicating a contingent relationship dependent on firm-specific contexts. The study suggests implementing regulations mandating minimum sustainability disclosure for large and profitable enterprises. Capacity-building initiatives for small private firms and the adoption of integrated reporting policies can enhance transparency. These outcomes contribute contemporary insights into corporate sustainability accounting in China’s evolving landscape. The implications extend to policy development and collaborative efforts to expand sustainability measurement and disclosure in Shanghai. Tailoring regulatory initiatives to firm profiles, such as size and profitability, enhances sustainability accounting practices. Targeted capacity-building programs, assurance mandates, and integrated reporting regulations improve the quality and usefulness of sustainability accounting information. Collaboration with the investor community is crucial for mainstreaming sustainability measurement and disclosure. This study deepens the understanding of sustainability accounting practices in Shanghai, an emerging economy financial hub. It provides insights for policy development, emphasizing firm and sector-specific factors driving sustainability accounting. Policymakers can promote transparency and responsibility by considering firms’ unique characteristics, fostering a more sustainable business environment.